2017
DOI: 10.1038/s41467-017-01531-2
|View full text |Cite
|
Sign up to set email alerts
|

An unusual endo-selective C-H hydroarylationof norbornene by the Rh(I)-catalyzed reactionof benzamides

Abstract: Hydroarylation is an environmentally attractive strategy which incorporates all of the atoms contained in the substrates into the desired products. Almost all the hydroarylations of norbornene reported to date involve an exo-selective reaction. Here we show the endo-selective hydroarylation of norbornene in the Rh(I)-catalyzed reaction of aromatic amides. The addition of sterically bulky carboxylic acids enhances the endo-selectivity of the reaction. The results of deuterium-labeling experiments show that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
0
18
0
2
Order By: Relevance
“…We recently reported on the Rh‐catalyzed reaction of aromatic amides that contain an 8‐aminoquinoline directing group with activated alkenes, such as acrylic esters, styrenes, α,β‐unsaturated lactones, maleimide, norbornene and N ‐vinylphthalimide . In a different system employing a picolinamide auxiliary, we described the alkylation reaction at C8‐position of 1‐naphthylamide using various alkenes .…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported on the Rh‐catalyzed reaction of aromatic amides that contain an 8‐aminoquinoline directing group with activated alkenes, such as acrylic esters, styrenes, α,β‐unsaturated lactones, maleimide, norbornene and N ‐vinylphthalimide . In a different system employing a picolinamide auxiliary, we described the alkylation reaction at C8‐position of 1‐naphthylamide using various alkenes .…”
Section: Methodsmentioning
confidence: 99%
“…Bidentate Amide Directing Groups CÀHb ond activation assisted by ab identate directing group is awell-established procedure for the functionalization of amides because of its strong coordination ability towards am etal center.O ne of the most versatile and reliable bidentate directing groups developed to date is the 8-aminoquinoline amide moiety,w hich was introduced by Daugulis and co-workers in 2005 for use in Pd-catalyzed CÀHarylation reactions. [187][188][189][190][191][192][193] In 2014, the Rh I -catalyzed alkylation of 8-aminoquinoline amides was first reported in the reaction of a,b-unsaturated esters (Scheme 53 a). [173][174][175][176][177][178][179][180][181][182][183][184][185][186] Theu tility of an 8aminoquinoline moiety for the Rh-catalyzed functionalization of amides discussed here was mainly reported by Chatani and co-workers in terms of various alkylation and alkenylation reactions.…”
Section: Aminationmentioning
confidence: 99%
“…[187] Av ariety of a,bunsaturated esters can be used in this reaction, with the desired products being produced in good to excellent yields. [191] Theresults of deuterium-labeling experiments suggested that commonly accepted mechanisms,such as hydrometalation or carbometalation, do not appear to be applicable for this reaction and that an uncommon rhodium-carbene species is generated from the norbornene. [192] Control experiments suggested that bidentate coordination and the presence of an acidic proton on the amide were required for the success of the reaction.…”
Section: Aminationmentioning
confidence: 99%
“…Der 8‐Aminochinolin‐Baustein kann leicht installiert und wieder entfernt werden, sodass sich viele Arbeitsgruppen auf diese dirigierende Gruppe konzentriert haben . Die hier diskutierte Anwendung des 8‐Aminochinolin‐Bausteins für die Rh‐katalysierte Funktionalisierung von Amiden geht hauptsächlich auf die von Chatani veröffentlichten Alkylierungs‐ und Alkenylierungsreaktionen zurück. Die Rh I ‐katalysierte Alkylierung von 8‐Aminochinolinamiden wurde erstmals 2014 bei der Reaktion von α,β‐ungesättigten Estern diskutiert (Schema a) .…”
Section: C‐h‐funktionalisierung Von Carbonsäurenunclassified
“…Kontrollexperimente legten nahe, dass für den Erfolg der Reaktion eine zweizähnige Koordination und die Gegenwart eines acidischen Protons am Amid erforderlich sind. Kürzlich wurde berichtet, dass die Kupplung von Benzamiden mit Norbornen zur ungewöhnlichen Bildung des endo‐ selektiven Kupplungsprodukts 180 führt (Schema d) . Die Ergebnisse der Deuterium‐Markierungsexperimente führten zu der Annahme, dass die gewöhnlicherweise angenommenen Mechanismen, wie Hydrometallierung oder Carbometallierung, bei dieser Reaktion scheinbar nicht auftreten und dass aus dem Norbornen eine ungewöhnliche Rhodium‐Carben‐Spezies gebildet wird.…”
Section: C‐h‐funktionalisierung Von Carbonsäurenunclassified